2016
DOI: 10.1016/j.sleep.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course of H1N1-vaccine-related narcolepsy

Abstract: Objective: To follow and analyze the clinical course and quality of life of Pandemrix H1N1-vaccinerelated narcolepsy (pNT1). Methods: Twenty-six drug-naïve confirmed pNT1 subjects completed Epworth Sleepiness Scale (ESS), Ullanlinna Narcolepsy Scale (UNS), Swiss Narcolepsy Scale (SNS), Rimon's Brief Depression scale (RDS), and WHO-5 Well-being index questionnaires near the disease onset and in a follow-up a minimum of two years later. The number of cataplexies and body mass index (BMI) were recorded. The effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Szakacs et al found that psychiatric symptoms seemed to be more frequent in PPN patients, but as there were 31 PPN and only 7 SN patients comparison between the groups was difficult (95).Our findings in Paper III, showing overweight /obesity in 54% of the children and 61% of the adults is in line with previous prevalence reports on BMI in patients with SN(12, 13,101). They also found a greater BMI in the SN group than in the PN group which they suspected was due to a greater age and longer disease durations in the SN group(165). The mean disease duration in our study was longer than in the study of Sarkanen, differing approximately 2 years.…”
supporting
confidence: 90%
“…Szakacs et al found that psychiatric symptoms seemed to be more frequent in PPN patients, but as there were 31 PPN and only 7 SN patients comparison between the groups was difficult (95).Our findings in Paper III, showing overweight /obesity in 54% of the children and 61% of the adults is in line with previous prevalence reports on BMI in patients with SN(12, 13,101). They also found a greater BMI in the SN group than in the PN group which they suspected was due to a greater age and longer disease durations in the SN group(165). The mean disease duration in our study was longer than in the study of Sarkanen, differing approximately 2 years.…”
supporting
confidence: 90%
“…It is possible that subjects with a more severe phenotype are diagnosed earlier after the vaccination than those with milder symptoms ( Table 4). The disease course between idiopathic and Pandemrix-associated narcolepsy seemed similar in a recent study [57]. Vaccine associated cases are characterized by high frequency of HLA DQB1*06:02, cataplexy and hypocretin deficiency.…”
Section: Discussionmentioning
confidence: 58%
“…Thus, we do not know how consistent UNS scores are between two visits without a change in health or symptoms of narcolepsy (test-retest reliability). We saw in our previous longitudinal study that there are great individual differences and heterogeneity in the evolution of UNS scores between individuals [18]. The result could also mirror heterogeneity of the disease itself.…”
Section: Discussionmentioning
confidence: 84%